Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Review - Page 330: 74



Work Step by Step

RECALL: (i) $(x+y)(x-y) = x^2-y^2$ (ii) $(x-y)^2=x^2-2xy+y^2$ Use rule (i) above where $x=4$ and $y=3a-b$ to have: $\\=4^2-(3a-b)^2$ Use rule (ii) above where $x=3a$ and $y=b$ to have: $\\=16-[(3a)^2-2(3a)(b)+b^2] \\=16-(9a^2-6ab+b^2) \\=16-9a^2-(-6ab)-b^2 \\=16-9a^2+6ab-b^2 \\=-9a^2-b^2+6ab+16$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.